Novel approach reveals genomic landscapes of single-strand DNA breaks with nucleotide resolution in human cells - Huifen Cao (Nature Communications, 2019)
Single strand breaks represent the most common form of DNA damage yet no methods to map them in a genome-wide fashion at single nucleotide resolution exist. Here the authors develop such a method and apply to uncover patterns of single-strand DNA “breakome” in different biological conditions.